A poética de Dona Caçula: autoria feminina e universo temático do Romanceiro Sergipano - Trindade, Antonio Marcos dos Santos (2021)
In this study, I propose to defend the thesis that the Romanceiro Sergipano (the book O Folclore em Sergipe), collection of traditional ballads collected by Jackson da Silva Lima and published by him in 1977, constitutes a great mestizo rhapsody, sung mainly by women. My hypothesis is, then, that the female universe, both in the authorship of the collection and its thematic field, is what structurally characterizes this award-winning collection of Ibero-Brazilian popular poetry. Through literary analysis (aesthetic) – that is: through the study of the literary plan of the transcriptions of the chants, as well as the presentation of some photographs and the analysis, among them, of one that presents a performance, considered by me as the real “form” of the genre –, I intend to show that the interpreters of the poems, among which are predominantly black and “brown”, although also white and “pardo” (brown), all coming from the most varied social classes, forming an arc that goes from beggar, prostitute and rural workers to public employees, far from being just passive carriers and transmitters of the tradition, they are rather truly authors of the poems they sing, leaving their stylistic, sexual and cultural marks in the ways in which they reconfigure thematic sequences, characterize the characters and guide the narratives to the outcome, constituting these steps what I am symbolically calling “The poetics of D. Caçula”, name of the interpreter who sang the gratest number of poems to collect. So, from this collection, I formed a poem corpus consisting of 51 versions of 10 ballads, 5 from the Iberian tradition plus 5 from the national tradition. They are: Juliana, O Conde da Alemanha, Leonora, Iria a Fidalga and A Moreninha (Iberian tradition), O Caso de João Alves Flor; Aninha; José e Maria; João e Maria and Marido Infeliz (national tradition). My approach, therefore, is not the historical-philological one, common in balladistic studies, concerned with finding the sources of the European literary archetypes of these popular chants. This type of approach leads to see the Brazilian versions of the ballads as “mistake”, in the sense of distancing themselves from their Iberian models. The approach I have in mind is the literary (poetic), which, considering the differences in the versions of those who sing them as copyright marks, “creative wander”, seeks to value them in the analysis of the thematic content, style and compositional structure of the texts, in order to understand them in their deep relations with Brazilian culture and literature and with authors, their interpreters. Thus, relying on several authors, including R. Menéndez Pidal, Ria Lemaire, Alvanita Almeida Santos, Paul Zumthor, amog others, I intend to defend the hypothesis that the traditional ballad with a “novelesque” theme is inextricably related to the female universe, in this way revolving, as a result, around conflicts referent to family issues – marriage, betrayals, frustrated loves etc. –, playing an ambiguous formative (playful and paidetic) role, in the identity constitution of the woman who sings it.